Tilapia Lake Virus (TiLV) Examination on Commodities of Tilapia (Oreochromis niloticus) - nadiatul husna (Journal of Aquaculture Science, 2020)
The increasing utilization of the potential for fishery commodities and the traffic of fishery commodities between countries and between areas in the Indonesian territory is an opportunity for the risk of entry and spread of fish pests and diseases. One of the pathogens that are acute in nature that can cause great harm is a virus. The virus that often attacks freshwater fish is the Tilapia Lake Virus (TiLV). Virus examination using conventional PCR methods, starting with necropsy, fixation, extraction, amplification, electrophoresis, and reading the results. The aim of this study was to detect the presence of TiLV infection in freshwater fish commodities using the Polymerase Chain Reaction PCR method. This research was conducted on 23 December 2019-27 January 2020 at the Fish Quarantine Station for Quality Control and Safety of Fishery Products in Yogyakarta. The samples examined were 14 samples of tilapia. Based on the test results, it was found that 2 positive samples contained TiLV RNA which showed a band at 250 bp length (base pairs) in tilapia seeds.Keywords: Tilapia Commodity, PCR method, TiLV.